Gene transfer to the patellar tendon - Gerich, Torsten G.; Kang, Richard; Fu, Freddie H.; Robbins, Paul D.; Evans, Christopher H. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 1997)
Growth factors have the potential to enhance native repair responses in ligamentous lesions. However, methods for applying these cytokines to sites of injury for extended periods are lacking. We suggest that local transfer of genes which encode the relevant healing factors merits investigation as a potential solution to this problem. In the present study, the retroviral vectors MFG lacZ and BAG lacZ neo r and adenovirus LacZ were evaluated for their ability to deliver genes to cells of ligamentous origin. The posterior and anterior cruciate ligaments, medial collateral ligament, semitendinosus tendon and patellar tendon were harvested from New Zealand white rabbits. Cells grown from these tissues were then investigated for their susceptibility to genetic alteration by these vectors in vitro. Based upon their ability to convert cells in culture to a lacZ(+) phenotype, adenovirus was the most effective vector in short‐term experiments. However, expression was transient. Although retrovirus gave lower initial transduction efficiencies, the percentage of transduced cells could be increased by the use of the selectable marker gene neo r . In an in vivo marker study, we injected adenovirus into the rabbit patellar tendon. Transduced cells could be observed preferentially in the subsynovial layer at a declining frequency over a 6‐week period. The allogeneic transplantation of in vitro retrovirally transduced fibroblasts into the patellar tendon resulted in a greater number of transduced cells. Although the number of lacZ(+) cells declined with time, positive cells were still present 6 weeks after transplantation. Furthermore, the transplanted cells, unlike cells transduced in situ with adenovirus, migrated from the injection site and integrated into the crimp of the tendon.